1999
DOI: 10.1016/s0005-2736(99)00097-8
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence, absorption and electron spin resonance study of bacteriochlorin a incorporation into membrane models

Abstract: Analysis of the bacteriochlorin a absorption spectra suggests the existence of a monomer-dimer equilibrium, particularly intense in phosphate buffer and favored by a decrease of the pH. The dye in methanolic solution is predominantly in monomeric form. Fluorescence and electron spin resonance nitroxide spin labeling measurements indicate that incorporation into the lipid phase of dimyristoyl-L-alpha-phosphatidylcholine liposomes induces dye monomerization. Moreover, the molecules are bound in the external surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 33 publications
(35 reference statements)
2
26
0
Order By: Relevance
“…In general, incorporation of a dye in liposomes led to an increase of the fluorescence intensity in comparison with its intensity in aqueous solutions. This increase was studied as a function of the lipid concentration at constant PPME concentration (2.5 µM) in order to establish the ratio between lipids and dye at which all PPME in suspension may be considered as bound to liposomes 33 . Fig.…”
Section: Determination Of Ppme Incorporation Limit In Liposomesmentioning
confidence: 99%
“…In general, incorporation of a dye in liposomes led to an increase of the fluorescence intensity in comparison with its intensity in aqueous solutions. This increase was studied as a function of the lipid concentration at constant PPME concentration (2.5 µM) in order to establish the ratio between lipids and dye at which all PPME in suspension may be considered as bound to liposomes 33 . Fig.…”
Section: Determination Of Ppme Incorporation Limit In Liposomesmentioning
confidence: 99%
“…It has also been shown that solubilization of BCA in liposomes induces dye monomerization. 11 Oxygen consumption measurements carried out with a Clarke electrode in water and in liposome solutions indicate that the production of 1 O 2 is strongly influenced by the dye aggregation state since it seems that only the monomeric species is appreciably photoactive. 12 Indeed, monomerization of BCA by solubilization within liposomes increases the PDT activity and is accompanied by an enhancement of singlet oxygen production.…”
Section: Introductionmentioning
confidence: 99%
“…The medium where BCA is solubilized influences not only the 1 O 2 production but also the dye aggregation properties (8). In methanol, BCA is monomeric, and no aggregation is observed below 5 3 10 25 M (8). In phosphate buffer (pH 7), BCA is strongly aggregated in its dimeric form.…”
Section: Introductionmentioning
confidence: 99%
“…In phosphate buffer (pH 7), BCA is strongly aggregated in its dimeric form. The dimerization constant was estimated to be 10 6 M 21 (7,8). The solubilization of BCA within DMPC liposomes induces dye monomerization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation